2019
DOI: 10.4274/eajem.galenos.2018.94830
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Trauma Scoring Systems in Pediatric Trauma Patients

Abstract: Introduction Trauma is one of the major causes of death among all age groups. It is the leading cause of death and disability among children older than 1 year of age (1). In addition to designing pre-hospital and hospital trauma organizations, taking meticulous preventive measures and providing public education are greatly important for efforts aimed at reducing trauma-related mortality (2). Initial assessment and management of multi-trauma patients is a difficult task requiring a rapid and systematic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Comparative evaluations have demonstrated similar performance to well-established trauma severity illness scores utilized in industrialized western nations: Pediatric RISk of Mortality (PRISMIII), Pediatric Index of Mortality 2 (PIM2), and the PEdiatric Logistic Organ Dysfunction (PELOD) score [9]. Similarly, BIG performed well compared to the New Injury Severity Score (NISS), TRauma and Injury Severity Score (TRISS), and Probability of Survival 2014 (PS14) scores in a pediatric population from Turkey and Syria [10]. Evaluating the newer BIG score and other pediatric trauma scoring systems for their ability to predict risk of infection could extend their utility.…”
Section: Pediatric Trauma Injury Severity Scoringmentioning
confidence: 66%
“…Comparative evaluations have demonstrated similar performance to well-established trauma severity illness scores utilized in industrialized western nations: Pediatric RISk of Mortality (PRISMIII), Pediatric Index of Mortality 2 (PIM2), and the PEdiatric Logistic Organ Dysfunction (PELOD) score [9]. Similarly, BIG performed well compared to the New Injury Severity Score (NISS), TRauma and Injury Severity Score (TRISS), and Probability of Survival 2014 (PS14) scores in a pediatric population from Turkey and Syria [10]. Evaluating the newer BIG score and other pediatric trauma scoring systems for their ability to predict risk of infection could extend their utility.…”
Section: Pediatric Trauma Injury Severity Scoringmentioning
confidence: 66%
“…21 Sultanoğlu et al hypothesized that the BIG score was superior to RTS and PTS to predict the mortality ratio. 7 In the study conducted with pediatric blunt trauma patients, probability of survival was found to be high in patients with the BIG score <18. 22 In this research, a reverse linear correlation was detected between BIG score and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…After base deficit, INR, and GCS were found to be significantly related to pediatric mortality after trauma, the BIG score was developed in 2011. 7 The BIG score has been used in adult trauma patients and has been found to be useful in accurately predicting mortality. 21 Sultanoğlu et al hypothesized that the BIG score was superior to RTS and PTS to predict the mortality ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Several trauma scoring systems were developed to reduce the rate of morbidity and mortality in children with trauma, including ISS and GCS [12]. After admission to the hospital, the main mortality risk factors include being male, under 15 years of age, and coma.…”
Section: Discussionmentioning
confidence: 99%
“…Scoring systems provide information about the relationship between treatment and outcomes [11]. Injury Severity Score (ISS) is the "gold standard" among anatomical injury severity indicators in the trauma population [12,13]. Glasgow Coma Score (GCS), one of the physiological scoring systems used in patient follow-up from the time of admission, is a simple, objective scoring system that can indicate consciousness level and is commonly used in the reliable evaluation of the degree of coma [14].…”
Section: Introductionmentioning
confidence: 99%